Effect of the strategy of look before you hear in interactive thinking and learning some types of passes in basketball for students - Doaa Muhibaldein, A.; Nooralhuda Sattar, J.; Farah Alaa J. (Proximus Journal of Sports Science and Physical Education, 2024)
Teaching strategies are mental processes that help learners perceive and acquire knowledge. They also enable them to store and stabilize information and give them the ability to organize information in memory, which helps them facilitate the process of recalling it. Modern strategies have emerged in teaching, including experiential learning strategies that may have an effective role in making the student the focus of the educational process. This type of learning comes from the fact that it achieves the student`s desires and needs and increases his ability to carry out evaluation, effective planning, and observation, all of that. It leads to the student learning a new skill and forming new positive attitudes or thinking in a new way away from the state of stress and anxiety